Benthic macroinvertebrate communities in sites with native forest presence and absence in north Patagonia - Ríos-Escalante,Patricio De los (2020)
ABSTRACT The benthic fauna in northern Patagonian streams is characterized by presence of water quality indicator species. The aim of the present study was characterized the benthic communities in streams associated to sites with presence of Nothofagus forests and with human intervention without Nothofagus forests using null models in ecology, unified neutral theory of biodiversity (UNTB) and unweighted pair group method with arithmetic mean (UPGMA). The results of species co-occurrence null model revealed that species associations are random, whereas the results of niche overlap null models revealed the presence of niche overlap. The UNTB results revealed low species number. The results of UPGMA revealed that species composition is specific for each site existing marked differences. The exposed results agree with results observed for central and northern Patagonian Chilean rivers, where the species composition is variable in according to surrounding basin properties and seasonal conditions.